A Meta-Analysis On The Effect Of Ethnomathematics To Students’ Ability In Geometry - Wahyu Ridlo Purwanto; Zaenuri Zaenuri; Wardono Wardono; Iwan Junaedi (International Conference on Science, Education, and Technology, 2022)
Geometry skills are fundamental in studying mathematics in three dimensions. In schools, it is expected to make schemes of methods and solutions so that students in junior high school can more easily understand geometry lessons by providing tangible examples in students' environments. One of the solution keys to mathematics lessons, especially in geometry, is to combine it with ethnomathematics. In this study, a meta-analysis is reviewed to present an empirical synthesis of studies designed to deliver a systematic design of ethnomathematics related to the meta-analysis's geometric learning education submission, empirical studies are used on the analysis of journal articles from 2015-2021. This research is focused on empirical studies using mixs-methods this meta-analysis conduct to gain knowledge of ethnomathematics on the general effect of students' geometric skills. This method aims to examine and combine all pertinent studies, both published and unpublished, so that a weighted mean effect size would be derived. This meta-analysis aims to review the quantitative results of empirical studies of the effect of ethnomathematics in conveying students' geometric abilities The results of this study are statistically significant with small mean scores on effect sizes and heterogeneity test results between studies. Linear models are used to describe the independent variables that affect all effect sizes. The meta-analysis results were obtained. The effect of ethnomathematics has a positive impact on learning geometry in secondary schools. Ethnomathematics can be used as a solution to learning geometry to improve students' geometry skills.